Growth dimension and DNA analysis of Bulinus snail from River Wudil, Kano State Nigeria - Rasheed Olatunji Moruf; Halima Abdullahi Muhammad (Syiah Kuala University, 2023)
The growth pattern and DNA yield and purity of Bulinus. globosus from River Wudil, Kano State, were investigated using standard methods. The mean ranges in mm from 7.9±2.9, 5.7±2.5, 4.8±1.8, 3.4±1.2, 1.5±0.2, 1.6 ± 0.0, 2.4 ± 0.2, 1.2 ± 0.1, 1.4 ± 0.1, 65.8 ± 1.9 and 22.2 ± 0.4 were recorded for length, width, aperture height, aperture width, height width ratio, height and aperture height ratio, height and aperture width ratio, width and aperture height ratio, aperture height and aperture width ratio, shell weight and flesh weight. About 33.7 % of weight of the snail is made up of flesh by weight. The value of “b” showed that B. globosus exhibited a negative allometric growth pattern while the correlation coefficient (r) in all the shell variables were below 1, indicating a weak correlation between the parameters. Mean DNA yield and purity were 120.03 ± 5.10 ng/µl and 1.81 ± 1.21. The DNA yield in this study is well above the minimum standard and the pure extracts are good enough for further DNA analyses.